Immune-mediated hemolytic anemia (IMHA) (Revista Sistemas de Producción Agroecológicos, 2014)
The immune-mediated hemolytic canine anemia (IMHA) is caused by the early destruction of erythrocytes due to the fixation of antibodies to own or foreign antigens on cell membrane surface; consequently, the anemia appears to be a result of the inability of the bone marrow to compensate the high red cell destruction. This disease affects females of medium age with major frequency and to every breed. The clinic manifestations usually are on physical examination and complementary test showing the hypoxia tissue caused by the anemia; as well as haemostatic alterations if there is concurrent thrombocytopenia. The IMHA can be confirmed by two ways: 1) the presence of anemia, autoagglutination and spherocytosis in the blood smear, and 2) the direct test of Coombs. The latter detects the antibodies on the erythrocyte membranes. The main complications are the disseminated intravascular coagulation (DIC) and thromboembolic disease, in particular the pulmonary thromboembolism (PTE). The treatment of the canine IMHA is based on the administration of corticosteroid with or without alkylating, together with the therapy of support necessary in each one of the cases, and controlling or eliminating the primary disease. In general, the death rate of the canine patients with IMHA change from 20 to 50%, but it can be higher than in fulminating and complicated presentations.
Keywords: hemolytic anemia; canines; blood